(untitled) (Research, Society and Development, 2021)
The rural settlements of the agrarian reform are constituted in production units conceived to aim at environmental sustainability and improving the quality of life in the rural environment. It arises, therefore, due to the need for an endorsement of sustainability with three main focuses, either environmental, or economic and social. The purpose of this study was to analyze the socioeconomic and environmental sustainability indicators of two rural assemblies in the State of Mato Grosso. To this end, bibliographic and documentary surveys have been carried out on sustainable development, agrarian reform and rural settlements. Methodologically, it is used the Sustainability Barometer, a ferramenta that gathers indicators of dimensions related to being in the environment and being human. Foram analyzed, 3,857 rural lots, of 39 settlements, totaling 11 municipalities of the state of Mato Grosso. The results show that the degree of sustainability obtained was obtained from an Intermediate degree, on a scale: Bad (Unsustainable), Poor (Potentially Insustentável), Medium (Intermediate), Bom (Potentially sustainable) and Very Good (Sustainable). Factors that negatively influence only or little access to socio-governmental programs and a high rate of use of pesticides in two established production areas. Among the factors that positively influence your health and education.